Booklet ‘Pakuli to Kaili’: An Innovative Civics Learning Media Utilizing Local Wisdom to Enhance the Pancasila Student Profile - Shofi Nurul Fath; Sunarto Amus; Hasdin Hasdin; Jamaludin; Idrus; Lukman Nadjamuddin (Jurnal Pedagogi dan Pembelajaran, 2025)
The main challenge in Civic Education lies in the weak integration of Pancasila values with local wisdom, which results in low students’ awareness of cultural identity, particularly the local wisdom of the Kaili ethnic group. This study aims to develop and evaluate the Pakuli To Kaili booklet as an innovative and contextual learning medium. This study employed a Research and Development (R&D) approach using the ADDIE model. The participants consisted of 35 students, 2 teachers, and 1 media expert as a validator. Data were collected through interviews, observation checklists, expert validation sheets, and student–teacher questionnaires. Instrument validity was analyzed using item–total correlation and reliability using Cronbach’s Alpha, while overall data were analyzed descriptively. Expert validation instruments were used to assess the feasibility of the Pakuli To Kaili booklet as a local wisdom–based Civic Education learning medium. The instruments were designed in the form of a four-point Likert-scale questionnaire (1–4), covering content feasibility, language, presentation, and media design aspects. Validation was conducted by learning media experts and Civic Education subject-matter experts.The results indicate that the Pakuli To Kaili booklet is valid, practical, and effective, and received positive responses from both teachers and students. The booklet was shown to enhance students’ understanding of Pancasila values and strengthen the Pancasila Student Profile based on local wisdom, indicating its potential as a sustainable alternative for contextual Civic Education learning.